Effect of organic matter and of a nitrification inhibitor "AM" on the uptake of 15NH4 and 15NO3 by maize - Saito, Siu Mui Tsai; Neptune, André Martin Louis (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
The present experiment, carried out in greenhouse, had the aim to verify the effect of the forms 15NH4 and 15NO3 in presence or absence of organic matter and of the nitrification inhibitor "AM" (2-amino-4-chloro-6-methyil-pyrimidme) in dry matter weight and nitrogen content of the plant derived from soil and from fertilizer. The test plant was the hibrid maize Centralmex. The fertilizers (15NH4)2SO4 and Na15NO3, were added in two levels: 40 and 120 kg N/ha, with 1,02% of 15N and 1,4% of 15N in excess, respectively. Three soils of different physical and chemical characteristics were used: Regossol «intergrade", Latossol Roxo and Podzolizado de Lins e Marília var. Marília. The results showed a better effect of the nitrate form, mainly in the presence of the organic matter, on the absorption of nitrogen by the plants. The presence of organic matter contributed to increase the use of the nitrogen fertilizer in the soils Regossol and Podzolizado, but did not show any significative effect in the Latossol Roxo. The nitrification inhibitor "AM" was neither effective on dry matter weight nor increased the efficiency of the fertilizer. There are also evidences that the presence of the organic matter increased the "A" Value of Latossol Roxo and Podzolizado, but this did not happen in the Regossol, because in this soil, the use of nitrate form alone was better than the treatments with organic mater and "AM". The high "A" Values obtained in the experiment can be attributed, in part, to the short period of the experiment, The "A" Value may not express the real nutritive potential of the soil nitrogen.